Splenic abscess presenting as a case of pneumoperitoneum: a rare presentation - Raju, T. R. S. Prudhvi; Paruthy, Shivani B.; Mohan, Sajith K.; Wani, Dawood I.; Bajwa, Jaspreet S.; Anand, Arun; Singh, Kashinath; Das, Anirban; Siwach, Rajguru (International Surgery Journal, 2021)
Pneumoperitoneum is more pathognomonic of ruptured hollow viscera which requires urgent surgical intervention. But uncommon surgical entities may present with pneumoperitoneum. Splenic abscess is a relatively rare medical condition that results from bacteraemia. Pneumoperitoneum in a ruptured splenic abscess is very uncommon and is often misdiagnosed as a perforation. Spontaneous rupture of splenic abscess is a life-threatening emergency mandating early surgical intervention. We report a case of ruptured splenic abscess which presented with peritonitis and pneumoperitoneum, managed successfully by splenectomy.